Agarose capsules as new tools for protecting denuded mouse oocytes/embryos during handling and freezing-thawing and supporting embryonic development in vivo. Issue 1 (December 2017) - Nagatomo, Hiroaki; Yao, Tatsuma; Araki, Yasuyuki; Mizutani, Eiji; Wakayama, Teruhiko
Abstract Oocytes without a zona pellucida (ZP) often occur as a result of congenital or operational effects, but they are difficult to handle, and embryonic survival is low. Such zona-free (ZF) oocytes are therefore not used in clinics or laboratories. Furthermore, in the laboratory, removal of the ZP is often necessary for genetic manipulation by viral infection or twin production by blastomere separation, but adverse effects on development have been reported. It would therefore be extremely valuable if the embryo could be covered with a structure similar to that of the ZP. In this study, we sought to determine whether an agarose capsule could serve as a substitute for the ZP. Our results indicate that embryos derived from these agarose capsules were able to develop normally, and could be transplanted to obtain viable offspring, without having to remove the agarose capsule. Furthermore, before compaction, the agarose capsule embryos exhibited good freezing tolerance, and survival rate was extremely high compared to ZF embryos. Thus, agarose capsules represent a valuable tool for utilizing oocytes and embryos that lack a ZP, both in a clinical and livestock setting.